2011
DOI: 10.4238/2011.october.19.2
|View full text |Cite
|
Sign up to set email alerts
|

Methodology Optimization of PCR conditions to amplify Cyt b, COI and 12S rRNA gene fragments of Malayan gaur (Bos gaurus hubbacki) mtDNA

Abstract: ABSTRACT. PCR has been extensively used for amplification of DNA sequences. We conducted a study to obtain the best amplification conditions for cytochrome b (Cyt b), cytochrome c oxidase I (COI) and 12S rRNA (12S) gene fragments of Malayan gaur mtDNA. DNA from seven Malayan gaur samples were extracted for PCR amplification.Various trials and combinations were tested to determine the best conditions of PCR mixture and profile to obtain the best PCR products for sequencing purposes. Four selected target factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Additionally, this gene has an evolutionary rate that is almost similar to that of mitochondrial DNA itself 17 . Gel analysis can give a broad classification of species by the size of the amplicons but is not as specific as sequencing the amplicon.…”
mentioning
confidence: 96%
“…Additionally, this gene has an evolutionary rate that is almost similar to that of mitochondrial DNA itself 17 . Gel analysis can give a broad classification of species by the size of the amplicons but is not as specific as sequencing the amplicon.…”
mentioning
confidence: 96%
“…According to Troast et al (2016), applications of the COI locus alone failed to postulate population structures within species accurately. Thus, we propose that future studies at the population level should exploit other mtDNA gene sequences such as cytochrome b and D-loop regions that have been proven to analyze taxa at population levels (Rosli et al 2011;Ang et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of these genes occurred 24 h earlier than CD4 and CD8 surface protein expression, which suggested that they were upregulated as a downstream effect of T cells activation. 12S ribosomal takes part in cellular surface molecular translation and synthesis in the early stage of T cell activation [20][21][22]. MHC-III (hsc70t) is a participant in the cytotoxic cell activation process by coding complement C2, C3 and B factor [23,24].…”
Section: Discussionmentioning
confidence: 99%